Treaties Nobody Counted On - Boast, Richard (Victoria University of Wellington Law Review, 2011)
This article is based on the author’s inaugural professorial lecture delivered at Victoria University of Wellington in March 2011. The author’s subject is treaties and treaty-like agreements, entered into between the New Zealand government and Māori after the Treaty of Waitangi.